Application of Response Surface Methodology for Combination of Herbal Extracts Against Antioxidant and Antipsoriatic Activity (Asian Journal of Pharmaceutics (AJP), 2020)
Aim: The present paper modeled combination of three herbal extracts, extract from the seed of Carica papaya, lyophilized water of Cocos nucifera, and extract from the stem of Ichnocarpus frutescens to evaluate their free radical scavenging activity, using Box-Behnken design response surface methodology (BBD-RSM), a statistical technique designed to optimize compositions that we applied in a novel manner to design combinations of herbal extracts for better antioxidant and antipsoriatic activity. Material and Methods: A BBD-RSM design using three factors and three levels were selected to optimize the ratio of three herbal extracts. Effect of three independent factors, that is, dry weight of C. papaya seed extract (ethanolic), dry weight of lyophilized coconut water, and dry weight of Ichnocarpus extract (hydroalcoholic) was studied on two dependent responses, that is, superoxide dismutase and 2,2-diphenyl-1-picrylhydrazyl activity. Results and Discussion: Combining herbal extracts in optimum ratio have shown synergistic potential against oxidative stress and for free radical scavenging activity. Combination therapy has been shown to be effective in preventing many disorders as compared to their individual potential for cure. The analysis of variance was performed to evaluate the significant differences between the independent variables. BBD-RSM allows for extrapolation of data from three or more compounds in variable ratio combinations. Conclusion: It has been proved that the optimized herbal extracts in a proper amount have significant potential against antioxidant and antipsoriatic activity.